The Duals of the 2-Modular Irreducible Modules of the Alternating Groups - Murray, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
We determine the dual modules of all irreducible modules of alternating groups over fields of characteristic 2.